The Practice and Effect of Multinational Enterprises' Media Strategy in Creative Cities: A Case Study of Hong Kong and Singapore - Wang, Qixuan (Transactions on Economics, Business and Management Research, 2024)
With the accelerated development of globalization, creative cities have gradually become an important area for the strategic deployment of multinational enterprises. The purpose of this study is to explore the media strategies adopted by multinational enterprises in creative cities, such as Hong Kong and Singapore, and their practical effects. Through in-depth analysis of the two market environments, combined with qualitative and quantitative research methods, including in-depth interviews, questionnaires and case studies, this paper reveals the characteristics and differences of the media strategies developed and implemented by multinational enterprises in different cultural contexts. The results of the study show that although Hong Kong and Singapore are both highly developed economies, due to their unique cultural and social characteristics, companies need to consider local consumer behavior patterns, language habits and media consumption trends when formulating media strategies. In addition, the support degree of government policies also directly affects the effectiveness of the strategy. Through the comparative analysis of the practical effects of the two places, this study provides valuable insights for enterprises to better adapt to the local market in the process of globalization, and puts forward corresponding strategy suggestions. Finally, this paper provides a new perspective for understanding the media strategies and influencing factors of multinational enterprises in creative cities.